Amorphisation of Free Acid Ibuprofen and Other Profens in Mixtures with Nanocellulose: Dry Powder Formulation Strategy for Enhanced Solubility - Athanasios Mantas; Valentine Labbe; Irena Loryan; Albert Mihranyan (MDPI AG, 2019)
The formulation of arylpropionic acid derivatives (profens), which are poorly soluble Biopharmaceutical Classification System (BCS) Type II drugs, has a strong impact on their therapeutic action. This article shows that heat-treated powder mixtures of free acid profens with high surface area Cladophora cellulose induces drug amorphization and results in enhanced solubility and bioavailability. Similar mixtures produced using conventional low surface area cellulose, i.e., microcrystalline cellulose, does not produce the same effect. The concept is thoroughly described and links the solid-state characterization data, such as differential scanning calorimetry, X-ray powder diffraction, and Fourier-transform infra-red spectroscopy, with in vitro dissolution in biorelevant media and in vivo pharmacokinetic analysis in rats. The concept is demonstrated for several substances from the profens group, including ibuprofen (main model drug), ketoprofen, flurbiprofen, and naproxen. The presented approach opens new ways to produce solid dosage forms of profen drugs in their free acidic form as alternatives to existing analogues, e.g., drug-salt conjugates or soft gel liquid capsules.